2015
DOI: 10.3390/toxins7103977
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adsorption and Flocculation Properties of Natural Clays to Remove Prorocentrum lima

Abstract: High accumulations of phytoplankton species that produce toxins are referred to as harmful algal blooms (HABs). HABs represent one of the most important sources of contamination in marine environments, as well as a serious threat to public health, fisheries, aquaculture-based industries, and tourism. Therefore, methods effectively controlling HABs with minimal impact on marine ecology are required. Marine dinoflagellates of the genera Dinophysis and Prorocentrum are representative producers of okadaic acid (OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition to particle size, shape (tube-shaped or spherical), surface electrical properties, and environmental pH, it has been reported that absorption sites play an important role in clay flocculation [28][29][30]. Recently, some properties of the particle surface, such as adhesion and rigidity, which also affect the flocculation efficiency, are also receiving much attention [31][32][33].…”
Section: Characteristics Of Nc and MCmentioning
confidence: 99%
“…In addition to particle size, shape (tube-shaped or spherical), surface electrical properties, and environmental pH, it has been reported that absorption sites play an important role in clay flocculation [28][29][30]. Recently, some properties of the particle surface, such as adhesion and rigidity, which also affect the flocculation efficiency, are also receiving much attention [31][32][33].…”
Section: Characteristics Of Nc and MCmentioning
confidence: 99%
“…Direct contact with contaminated seawater or inhalation of aerosolized biotoxins can lead to intoxications considered a direct impact of HABs on human health (Berdalet et al, 2016 ; Durando et al, 2007 ). Many species belonging to the Ostreopsis and Prorocentrum genera are able to synthetize potent toxins such as palytoxins (PLTXs), ovatoxins (OVTXs) and okadaic acid (OA)/dinophysistoxins (DTXs) (Karafas et al, 2015 ; Lewis et al, 2018 ; Louzao et al, 2015 ; Nascimento et al, 2016 ; Scalco et al, 2012 ; Wakeman et al, 2015 ; Wang et al, 2015 ). Other toxins are synthesized by other dinoflagellates belonging to the Coolia and Amphidinium genera, but they have never been demonstrated as having caused human poisoning (Holmes et al, 1995 ; Pagliara & Caroppo, 2012 ; Rhodes & Thomas, 1997 ; Rhodes et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, removal of Co(II) from industrial effluents is crucial. Several different methods exist to remove Co(II), including chemical precipitation, ion-exchange, coagulation, flocculation, and reverse osmosis [ 4 , 5 , 6 , 7 ]; unfortunately, most of these methods are expensive and/or environmentally unfriendly. Adsorption has been emerging as an effective technique for removing Co(II) and has many advantages, such as being high efficiency, environmentally friendly, and cost-effective [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%